Caregiving Relationships: A Gendered Perspective on Care Time in Italy - Boccacin, Lucia; Nanetti, Sara (Italian Sociological Review, 2025)
This contribution seeks to empirically explore the forms of informal caregiving in Italy, focusing on the relational dimensions and the gendered configurations that shape its sustainability and meaning. The study investigates how gender differences manifest in the distribution, experience, and narration of care, and examines the role played by family and friendship networks in supporting caregivers. Using a mixed-method design – structured in two phases, qualitative and quantitative – this article presents the findings of the qualitative research, conducted through dyadic interviews with caregivers of older adults and their reference persons. The study highlights a pronounced gender imbalance in the distribution of care work, with women bearing a heavier quantitative and emotional burden. Support networks, both formal and informal, play a decisive role in the sustainability of caregiving, yet they remain uneven in scope and quality. Male narratives tend to frame care as a functional and circumscribed intervention, whereas female narratives portray it as an all – encompassing and identity – defining experience. The integrated analysis shows that caregiving is not merely an assistive activity, but a situated relational process, in which identity, reciprocity, and recognition are deeply intertwined.